Metabolomic Profiling of Phloem Sap from Different Pine Species and Implications on Black Capuchin - Silva, Lorena Mara A.; Alves Filho, Elenilson G. Alves; Rodrigues, Tigressa Helena S.; Louredo, Francisca Jamila C.; Zocolo, Guilherme J.; Canuto, Kirley M.; Mikich, Sandra B.; Liebsch, Dieter; Almeida, Adriana de [UNESP]; Brito, Edy S. de (Springer Nature, 2022)
In most commercial pine farms in southern Brazil, black capuchin causes damage to wood and financial losses when it removes bark from some pine species to feed upon underlying vascular tissues. Therefore, this study aimed to evaluate the variability of the primary metabolites of phloem saps from 10 different species of pine by NMR spectroscopy, as well as the aroma compounds using SPME–GC–MS. Each technique provided a different set of metabolites that we can correlate to monkey predilection. The PCA showed monosaccharide (detected by NMR) and α-pinene (pine-like and resinous flavor descriptors) as attractive compounds for monkeys. On the other hand, the low content of monosaccharide and the high content of β-phellandrene (citrus odor descriptor) was observed in less attacked pine species (P. patula). The data fusion on primary metabolites and aroma compounds corroborated the individual analyses, complementing the comprehension of the monkey predilection. Thus, P. elliottii was an avoided tree even with high content of sugars possibly due to its high content of β-phellandrene (citrus odor). The results are useful for further behavioral studies to determine the role that each highlighted metabolite plays in chemically mediated animal-plant interactions.
Keywords: Capuchin monkey; Data fusion; NMR; Phloem sap; SPME–GC–MS